Bare-metal stents across the Vater's ampulla is a safe method for patients with lower bile duct obstruction. Issue 45 (November 2017) - Mao, Xiao-Nan; Lu, Zai-Ming; Wen, Feng; Liang, Hong-Yuan; Guo, Qi-Yong
Abstract : Abstract: This study explored the effect of the implant position of stents across the Vater's ampulla on treatment outcomes in patients with lower bile duct obstruction. In the retrospective study, 41 patients with malignant obstruction of the lower bile duct and obstructive jaundice received percutaneous transhepatic biliary placement of bare-metal stents. Basic demographic data on patients, such as sex, age, and primary diseases, and follow-up data, including postoperative complications and jaundice-free survival, were recorded. The follow-up data on patients with an involved ampulla, patients with an uninvolved ampulla, patients with a stent across the ampulla, and patients with a stent at a site other than the ampulla were compared. Furthermore, prognostic factors for jaundice- free survival were investigated using Cox proportional hazards regression analysis. Among the 41 patients, 38 patients experienced subsiding of jaundice, whereas 3 cases had unsuccessful stent patency. Whether or not the ampulla was involved did not influence the incidence rates of postoperative complications and the jaundice-free survival time. Notably, when stents were placed across the ampulla, the jaundice-free survival time was significantly longer than when stents were placed at sites other than across the ampulla ( P < .05). Furthermore, placement of the stent across the ampulla or at other sites was an independent prognostic factor (hazard ratio = 0.154, 95% confidence interval 0.042–0.560, P = .005) for jaundice-free survival of patients. The current study revealed that the implant position of a stent across the ampulla resulted in maintenance of stent patency and prolongation of the jaundice-free survival time.